Aktivitas Antioksidan Dan Kandungan Flavonoid Minuman Ready To Serve dari Ekstrak Daun Cem-Cem (Spondias pinnata (Lf) kurz), Daun Pegagan (Centella asiatica (L) Urban) dan Daun Katuk (Sauropus androgunus (L)) - IDPK Pratiwi; AA Sri Wiadnyani (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2018)
This study aims to obtain the better combination of cem-cem leaf extract, katagan leaf and Pegagan leaf to produce a ready to serve beverage with higher antioxidant potency than its constituent component. The research design was a randomized complete design by treatment combination of ready to serve beverage extract is divided into 9 levels with the comparison between cem-cem leaves, katuk leaf and kola leaf is in the range of 4.3,2 (cem-cem leaves); 2.0; 1.5; 1.0; 0.5; 0.0 (leaf pegagan and katuk leaf). pH, TSS, total acid, ascorbic acid, total phenol, total flavonoid and antioxidants capacity were measured. The result showed the best characteristic flavonoid and antioxidants was the formula of beverage with a combination of 3.0% cem-cem leaf extract, 0.5% of pegagan leaf and 0.5% katuk leaves have pH 3.40, TSS 7.75, Vitamin C of 84.48 mg / 100g, total acid 0,0405%, antioxidant capacity value 219,61mgGAEAC / 100g, total phenol 14,12% and total flavonoid 166,41mgEK / 100g with IC value 50 238,69 ppm.